PENGARUH LIKUIDITAS BANK DAN KREDIT BERMASALAH TERHADAP TINGKAT KECUKUPAN MODAL - Carindri, Fransisca; Filona, Filona; Putri, Meita (Prosiding PESAT, 2013)
The Purpose of this study was to determine how the effect of Liquidity and NonPerforming Loans to bank capital adequancy. This research sampling using purposivesampling to commercial banks listed in Indonesia Stock Exchange and publish theirfinancial statements in the period 2010-2012. The samples used in this research were 93banks listed in Stock Exchange 2010-2012. Methods of analysis used linear analysismethods, the classical assumption and hypothesis testing were processed using SPSS 15.0software. The result obtained are Loan to Deposit Ratio and Non Performing Loannegatively affect the Capital Adequancy Ratio. Where the high value of bank’s LDR andNPL will decrease the bank’s CAR.